Study of some risk factors and C - reactive protein levels among patients with cardiovascular diseases - Al-Rubayie, Yaqoub; Dawood, Dawood; alwan, Adnan (Iraqi National Journal of Nursing Specialties, 2011)
Objective : To study the effect of some risk factors like age, smoking and Diabetes mellitus (DM) among patients withcertain cardiovascular diseases (Angina pectoris and Myocardial infarction), in addition to the assessment of the Creactiveprotein (CRP) in the sera of those patients.Methodology: The study was carried out on (100) subjects who were hospitalized in the Iraqi Center of heart Diseasesin Baghdad city and were suffering from Myocardial InfarcƟon (MI) (16) and Angina Pectoris (AP) (79) or from both (5)over a period from September 2009 to June 2010. The results of paƟents were compared with those of (30) healthyand age-matched individuals as a control group. Data were obtained from patients who were already diagnosed byspecialists through the use of questionnaire forms including information about age, gender and smoking. Venousblood samples were collected from both the patients and control group to estimate the levels of blood glucose and Creactiveprotein.Results: StaƟsƟcal results showed that the majority of angina paƟents were males within the age group (51-60) yearswith significant differences between males and females. The study also demonstrated that the incidence of (MI) and(AP) was higher among non-smokers in comparison with smokers. The study indicated that the majority of patientswith (MI) and (AP) were diabetic. Finally, the study showed that the levels of C-reactive protein among (MI) and (AP)patients were higher than its level among the control group with a highly significant difference.Recommendations: A large size of sample is recommended to be studied to confirm the results of this study. Study ofother factors such as hypertension, body mass index and lipid profile may be of value.